2017
DOI: 10.1136/bmjopen-2016-014099
|View full text |Cite
|
Sign up to set email alerts
|

Influence of premium versus value brand names on the smoking experience in a plain packaging environment: an experimental study

Abstract: ObjectiveTo examine the effect of branding, as indicated by brand name, on evaluation of the cigarette smoking experience.DesignBetween-subjects and within-subjects experimental study. Participants were randomly allocated to smoke a cigarette from a pack featuring a premium brand name and a cigarette from a pack featuring a value brand name. Within each condition, participants unknowingly smoked two identical cigarettes (either two premium or two value cigarettes).SettingAustralia, October 2014, 2 years after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…The data presented here form part of a larger study of AYAs' experiences of cancer care in Australia. 27 This was a cross-sectional, retrospective self-report survey on cancer care experiences. In brief, AYA cancer patients, aged 15 to 24 years, when diagnosed with any form of cancer (except early-stage melanoma*) were approached about the study by postal mail.…”
Section: Methodsmentioning
confidence: 99%
“…The data presented here form part of a larger study of AYAs' experiences of cancer care in Australia. 27 This was a cross-sectional, retrospective self-report survey on cancer care experiences. In brief, AYA cancer patients, aged 15 to 24 years, when diagnosed with any form of cancer (except early-stage melanoma*) were approached about the study by postal mail.…”
Section: Methodsmentioning
confidence: 99%
“…Skaczkowski, Durkin, Kashima, and Wakefield () and Buchanan, Kelly, and Yeatman () explain that part of marketing theory and strategy is to determine and dictate how experience and exposure affect the facts and figures that customers gather and use from different sources about a brand. The perception process is exclusively personal and possibly determined by the mixture of inner and outer drivers such as past experiences, exposure, expectations, and desires.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Understanding young customers' perception is particularly significant as they are early adopters of technology (Leung & Wei, 1999;Vishwanath & Goldhaber, 2003), they are known as opinion leaders, which leads to activate a vital mass of customers using technology (Valente & Rogers, 1995). Skaczkowski, Durkin, Kashima, and Wakefield (2017) and Buchanan, Kelly, and Yeatman (2017) explain that part of marketing theory and strategy is to determine and dictate how experience and exposure affect the facts and figures that customers gather and use from different sources about a brand. The perception process is exclusively personal and possibly determined by the mixture of inner and outer drivers such as past experiences, exposure, expectations, and desires.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent experiment in the post-plain packaging context in Australia found that smoking a cigarette from a premium pack enhanced taste compared to when the same cigarette was smoked from a value pack. Further, this occurred regardless of the type of cigarette (premium or value) actually being smoked [ 14 ].…”
Section: Introductionmentioning
confidence: 99%